Penggunaan LKM Untuk Menunjang Kegiatan Laboratorium Virtual Fisika Inti - Hidayati Hidayati; Masril Masril (Jurnal Penelitian Pendidikan IPA, 2019)
To improve the quality of the Nuclear Physics lectures in addition to understanding the material as knowledge aspect, students are also expected to practice for the skills. The Nuclear Physics lecture material is microscopic so it requires laboratory activities, but there is no suitable practical tools available in the laboratory of Physics Department, mathatics and science faculty, universitas negeri padang. Therefore, a virtual laboratory model was developed in this research which was supported by students' worksheet. The valid and practical students' worksheet have been obtained. Then, it was tried out to students who take the Nuclear physics lecture to see whether the students' worksheet are effective to support virtual laboratory activities. The research conducted is included in the type of quasi-experimental research. The population is students who take part in the Nuclear Physics lecture in semester January-June 2018. The samples were taken using Cluster Random Sampling techniques. Data on knowledge and skills competencies were analyzed using the t test at a real level of 0.05. Based on the results of data analysis, there were significant differences in the two sample classes. The results of the regression analysis indicate that there is a strong correlation between the use of students' worksheet to support virtual laboratory activities for knowledge and skills competencies.Keywords: Nuclear Physics, Students Worksheet, Virtual Laboratory